Developing A Human Resource Development Model For Women Entrepreneurs In Indonesian MSMEs - Harianto Simarmata; Aggi Panigoro Sarifiyono; Miftah Andita Abdurrohman (Universitas Indonesia Membangun (Inaba), 2026)
Women entrepreneurs in Indonesia hold a pivotal role in national economic resilience, yet they face complex structural and managerial challenges amidst post-pandemic digital transformation. While previous studies have addressed isolated aspects such as financial literacy or digital transformation, there is a significant research gap regarding a comprehensive framework that integrates human resource strategies with digital and psychological dimensions. This study aims to develop a Collaborative Human Resource Development (HRD) Ecosystem Model tailored for women-led MSMEs. Employing a qualitative integrative literature review approach, this study synthesizes findings from recent scholarly publications indexed in reputable academic databases. The literature was selected based on predefined inclusion criteria focusing on women entrepreneurship, human resource development, digital transformation, and MSME development. The results formulate a model consisting of four integrated dimensions: (1) entrepreneurial competency development, (2) digital capability enhancement—encompassing fintech and digital banking adoption, (3) collaborative social and institutional support systems to mitigate dual-role barriers, and (4) adaptive leadership and entrepreneurial resilience strengthening. The model emphasizes that successful digital transformation requires not only technical proficiency but also psychological readiness and supportive institutional ecosystems. Theoretically, this study bridges the gap between HRD and women's entrepreneurship literature in an emerging economy context. Practically, it provides a strategic roadmap for policymakers and financial institutions to design holistic empowerment programs that move beyond basic literacy toward sustainable digital ecosystem integration.